Exploration of Tuina Effect and Mechanism in Chronic Atrophic Gastritis Rats - Qu, Yujiang; Ma, Xinwen; Xuan, Zhijin (Turkish Journal of Gastroenterology, 2022)
Background: Chronic atrophic gastritis is a very common condition in the general clinical practice of gastroenterology. Tuina treatment is widely used clinically. The aim of our study was to investigate the mechanisms of tuina in rats with chronic atrophic gastritis. Methods: Fifty-six specific pathogen-free grade rats were employed for our study. They were divided into 5 groups and treated differ- ently. Body weight was recorded every week, and their small intestine propulsive ratio was measured after intragastric administration of carbon powder. Histopathological observation of gastric tissues was performed using hematoxylin and eosin staining. The levels of motilin and gastrin in serum were detected by enzyme-linked immunosorbent assay, and the expression levels of Bcl-2 and cytochrome C were measured by the western blot assay.Results: There was no significant difference in body weight and small intestine propulsive ratio between the chronic atrophic gastritis model group and the tuina group (P > .05). However, we can see some significant changes in histomorphology after treatment with tuina. For example, the atrophy of gastric mucosal epithelium and glands had improved, and the inflammatory cells infiltrating the lamina propria were decreased significantly. Moreover, the level of gastrointestinal hormone GAS was increased (P < .001), and there was no statistically significant difference in motilin, Bcl-2, and cytochrome-c after treatment with tuina (P > .05).Conclusion: Our research demonstrated the effectiveness of tuina treatment on chronic atrophic gastritis with a possible underlying mechanism that affected the secretion of gastric acid, which could provide some useful information for clinical application.